Identifying term interbank loans from fedwire payments data - Dennis Kuo; David Skeie; James Vickery; Thomas Youle (Federal Reserve Bank of New York, 2013)
Interbank markets for term maturities experienced great stress during the 2007-09 financial crisis, as illustrated by the behavior of one- and three-month Libor. Despite widespread interest in these markets, little data are available on dollar interbank lending for maturities beyond overnight. We develop a methodology to infer individual term dollar interbank loans (for maturities between two days and one year) by applying a set of filters to payments settled on the Fedwire Funds Service, the large-value bank payment system operated by the Federal Reserve Banks. Our approach introduces several innovations and refinements relative to previous research by Furfine (1999) and others that measures overnight interbank lending. Diagnostic tests to date suggest our approach provides a novel and useful source of information about the term interbank market, allowing for a number of research applications. Limitations of the algorithm and caveats on its use are discussed in detail. We also present stylized facts based on the algorithm's results, focusing on the 2007-09 period. At the crisis peak following the failure of Lehman Brothers in September 2008, we observe a sharp increase in the dispersion of inferred term interbank interest rates, a shortening of loan maturities, and a decline in term lending volume.
Keywords: G01; G10; G21; 330; interbank market; loan; Fedwire; algorithm